Evolution of Regional income Disparities in Large European Economies - Malgorzata Kokocin´ska; Marcin Puziak (Revista de Economía Mundial, 2020)
Growing income disparities, affecting developing and developed countries alike, are a fact and, at the same time, one of the greatest economic challenges of modern times. Empirical studies in various areas usually compare countries using the Gini coefficient or the relationship between external and internal convergence. To a lesser extent, those analyses concern the long-term formation of the level of regional inequalities and the impact of major political or economic events on their course. The main objective of this work is to examine the direction of changes in income distribution in large European economies at NUTS2 level in 2000-2015. That period was marked by the occurrence of two non-standard events: the largest enlargement of the European Union to date and 2008 financial crisis, which, regardless of their positive or negative nature, put the studied countries in a new economic situation on each occasion. Therefore, the question arises whether those tipping points exerted an influence on the distribution of income in large European economies such as Germany, United Kingdom, France, Italy, Spain, and Poland. The results of the study indicate various directions of the changes in regional income disparities over the researched period.